Contribution of Planting Space and Harvesting Period on the Nutrient Compositions of Some OFSP Sweet Potato Varieties Grown in Southeast Nigeria Ultisol - Ojimelukwe, Philippa C; Ukom, Anthony N; Kalu, Obianuju O (Journal of Nutrients, 2018)
Two varieties of OFSP (Ex-Igbariam and Umuspo 3) planted at 20 cm x 1m, 30 cm x 1m and 40 cm x 1m and harvested after 12th and 16th weeks were analyzed for nutrient compositions. The statistical analysis showed wide variations in their proximate, mineral, vitamin and chemical contents. Moisture and protein contents were higher in 12th week of harvest than at 16th week irrespective of planting distance. Ash, fat, fibre and carbohydrate contents were higher at 16th week of harvest irrespective of the planting distance. Specifically, Umuspo 3 was higher in moisture and fat values while Ex-Igbariam was higher in ash, fibre, protein and carbohydrate. Calcium and vitamin C were higher at 12th week of harvest, while magnesium, potassium and vitamin B6 were higher at 16th week of harvest. Specifically, vitamin B6, phosphorus, magnesium and calcium were higher in some Ex-Igbariam lines especially in V4S3 than in Umuspo 3 lines. The chemical results showed that alpha amylase was higher in Ex-Igbariam V4S2 at 16th week of harvest while reducing sugar was higher in Umuspo 3 V1S1at 12th week of harvest. Total carbohydrate was higher in Umuspo 3 V1S1at 12th and 16th weeks of harvest. The general results indicates that the proximate, minerals, vitamin and chemical compositions of most of the variety lines were richer at 16th than at 12th week of harvest irrespective of planting distance. While 40 cm planting distance in V4S3 (Ex-Igbariam) gave higher yield of proximate, mineral, vitamin and chemical parameters, Umuspo 3 did not maintain a particular trend. Ex-Igbariam variety showed higher nutrient values than Umuspo 3 and may be recommended as a nutrient dense sweet potato staple for better nutrition.